(untitled) (Journal of Additive Manufacturing Technologies, 2021)
Lattice structures are becoming more and more attractive and preferred structures day by day because of their ultra-light weight properties with specific strength, load bearing capacity and time-cost-material efficiency. Due to their complex geometries it is impossible to generate these structures by conventional manufacturing methods. Laser powder bed fusion (LPBF), one of the most widely used and rapidly developing additive manufacturing (AM) method, provide opportunity to build up complex geometries. Ti6Al4V is commonly used AM material for biomedical lattice structure applications especially for bone implant researches. Mechanical properties of the lattice structures can be altered with lattice parameters (strut diameter, strut shape, unit cell dimensions and orientation). Compressive strength properties are the most critical concern for biomedical lattice structures as they are mostly employed under high compressive load. So, for developing functional, biomedical lattice geometries it is necessary to investigate the compression behavior of different lattice topologies. In this study, octahedroid, star and dodecahedron cubic lattice structures were manufactured with Ti6Al4V powder by LPBF technique for investigating their compressive behavior. Young moduli, maximum compression stress, experimental load values are determined and compared with literature. Mechanical properties of lattice structures were evaluated for bone implant applications.